Does Maternal Parenting Effects the Psychological Well Being of Adolescents? - Urooj Sadiq, Atiya Khatoon (Pakistan Journal of Psychology, 2012)
The aim of the present study was to determine the association between perceived maternal parenting styles and psychological problems among adolescents. On the basis of previous findings and literature review it was hypothesized that there would be a positive correlation between perceived negative maternal parenting styles and psychological problems among adolescent. Sample was selected from different private schools located in urban areas of Karachi and comprised of 100 adolescents (M=57; F=43) with the age range of 13-17 years (M=15.years). The Parental Authority Questionnaire (PAQ; Buri, 1991), and Strength and Difficulty Questionnaire (SDQ; Goodman, Meltzer, & Bailey, 1998) were administered to assess the variables of the study. Pearson product-moment correlation coefficient was computed to assess the relationship among variables. Results revealed that perceived permissive parenting style (r =.249, p<.05); and perceived authoritarian parenting styles (r=.222, p<.05) are positively correlated with psychological problems among adolescence.